Detection and quantification of VEGFR-1 in the nuclei of tumor cells by a new flow cytometry-based method. (1st January 2019) - Tyrsina, Ekaterina; Nikulitskiy, Sergey; Inshakov, Andrey; Ryabaya, Oxana; Tyrsin, Dmitry
Abstract: Flow cytometry using fluorescent antibodies (FC) is the method of choice for the quantitation of proteins expressed at the surface or inside the cell, but, however, does not allow to selectively measure nuclear expression. We therefore sought to develop a method for the extraction of intact cell nuclei, which can be used for their subsequent immunofluorescent analysis by FC. The studied protein was vascular endothelial growth factor-receptor-type 1 (VEGFR-1) which is important in tumor survival and metastasis. Two human cell lines, A431 (epidermoid carcinoma of skin with low invasive and metastatic potential) and BRO (highly aggressive amelanotic melanoma), were used as examples for tumor cells, and normal human fibroblasts PHF served as a control line. The quality of the extracted nuclei was assessed by their intactness and purity from cytoplasm. The high content of the nuclear markers (PCNA = proliferating cell nuclear antigen, lamin A/C) in the extracted nuclei with almost complete absence of the cytoplasmic β-tubulin demonstrated that the protocol can be used to obtain a pure suspension of single intact cell nuclei. The measurement of the nuclear VEGFR-1 content revealed that it was present only in tumor cell nuclei and that in more malignant BRO cells the receptor content was 1.75 times higher than in A431 ( p = 0.014). Thus, the developed method of extraction of cell nuclei for subsequent FC analysis is suitable for the quantitative evaluation of protein content in the native nucleus.